Contrast-enhanced ultrasound is a reliable and reproducible assessment of necrotic ablated volume after radiofrequency ablation for benign thyroid nodules: a retrospective study. (1st January 2022) - Yan, Lin; Li, XinYang; Xiao, Jing; Li, YingYing; Zhu, Yaqiong; He, Hongying; Luo, Yukun
Abstract: Purpose: To investigate the intra- and inter-observer reliability and agreement of contrast-enhanced ultrasound (CEUS) in measuring ablated volume (Va) after radiofrequency ablation (RFA) for benign thyroid nodules. Materials: This retrospective study evaluated 65 patients with 74 benign thyroid nodules who underwent RFA. Patients were followed up at 1, 3, 6, and 12 months and every 12 months thereafter. Two independent observers measured the Va using CEUS during the same follow-up visit. The intra- and inter-observer reliability was assessed using intraclass correlation coefficient (ICC) with 95% confidence interval. The Bland–Altman analysis was used to evaluate the inter-observer agreement, which was expressed as a mean difference with 95% limit of agreement (LOA). Results: No significant difference was found in Va measurements by the two observers with a mean follow-up time of 41.17 ± 16.80 months (all p  > 0.05). The intra- and inter-observer reliability were both excellent (ICC >0.90) at each follow-up period. The 95% LOA became wider over the follow-up period. The smallest 95% LOA was found at 1 month with a LOA from 0.8117 to 1.122, and the largest 95% LOA was from 0.5694 to 1.343 at 36 months. Conclusions: CEUS could provide a reliable and reproducible assessment of Va after RFA for benign thyroid nodules. In clinical post-ablation follow-up, the irregular morphology of ablated area and the variation by different observers could not affect the assessment of Va by CEUS.